Prediksi perubahan tutupan lahan di DAS Wae Batu Merah, Kota Ambon menggunakan Cellular Automata Markov Chain - Heinrich Rakuasa; Melianus Salakory; Marhelin Chostansa Mehdil (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2022)
The Wae Batu Merah watershed is located in the center of Ambon City and has the potential to trigger land-use change which will have an impact on decreasing water quality, water pollution, flooding, and erosion which will increase in the future. The objective of this study was to analyze land-cover changes in the Wae Batu Merah watershed in 2012, 2017, and 2022 and predict land cover in 2031. The method used was Cellular Automata Markov Chain (CA-MC) with 5 factors driving land cover changes including slope, elevation, distance from the river, point of interest (POI), and distance from the road. The results showed that from 2012, 2017, 2022, and 2031 the residental and open land-cover continued to increase in area, in contrast to the land-cover of agricultural areas and non-agricultural areas which a decrease in area. The kappa accuracy value in the model reaches 91%. The results of the model year 2031 show that residential land cover types have an area of ​​392.09 ha, open land has an area of ​​35.31 ha, agricultural areas have an area of ​​104.59 ha, non-agricultural areas have an area of ​​118.35 and aquatic land cover types have an area of 4.69 ha.